The Implementation of The Employability Skills Modules in a Computer and Network Engineering Expertise Program - Lestari, Ria Rosita; Syamwil, Rodia; Wibawanto, Hari (Journal of Vocational and Career Education, 2021)
A Vocational High School (VHS) is an institution that aims to prepare students to be ready for work. Therefore, the graduates must have employability skills. The purpose of this research was to find out the effectiveness of applying steamPjBL approach-based employability skill modules to Computer and Network Engineering (CNE) skills competencies. This research took a sample of 36 students of class X majoring in CNE at Ngraho Public VHS. This research and development employed the ADDIE model, which consists of five stages: (1) Analysis; (2) Design; (3) Development; (4) Implementation; and (5) Evaluation. The research stages included conducting observations, validating research instruments by experts, and conducting trials by distributing pretest and posttest questionnaires to experimental and control classes to find out any different learning outcomes. The analysis technique was carried out using the IBM SPSS Statistics 25. The results of the feasibility test showed that the module was very suitable for use and was considered valid with revisions; the results of the practicality test showed that the modules were very practical; and the results of the effectiveness test showed that the modules were quite effective to be used to train cooperation, communication, problem-solving, and adaptability skills